The Palestinian and Israeli Humanitarian Conflict Report in Instagram Caricatures: A Norman Fairclough Critical Discourse Analysis Study - Arrafi, Muhammad Naufal; Surur, Misbahus (Makassar State University, 2024)
Abstract. Many media reported Hamas' attack on Israel from various perspectives, some consider it terrorism and some call it a form of defense. The Instagram account @rahma_toons owned by an Amman-Jordan cartoonist, Ahmed Rahma, is always up to date describing the current conditions of the humanitarian conflict between Palestine and Israel through his caricature work. This research aims to reveal (1) text; (2) discursive practice; and (3) sociocultural practice contained in the humanitarian conflict against Palestine and Israel in @rahma_toons Instagram caricatures based on Norman Fairclough's perspective. This research uses a descriptive qualitative approach. Primary data sources are news related to the humanitarian conflict between Palestine and Israel in @rahma_toons Instagram caricatures. While secondary data is in the form of books and journal articles that support the research. The data collection techniques used were the screen capture technique, reading technique, and note-taking technique. The data analysis technique uses the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing related to the study of critical discourse analysis based on Norman Fairclough's perspective. The results of this study reveal (a) the text dimension of Instagram @rahma_toons uses vocabulary structures and language styles that are by the rules to convey caricature messages; (b) the discursive practice form of Instagram @rahma_toons conveys messages that attract audience attention and interaction; and (3) the socio-cultural form of Instagram @rahma_toons presents the latest news with interesting caricature visuals. The three dimensions of discourse cannot be separated from each other. Media coverage and commentary can have an impact on the views and responses of international organizations and the foreign policies of countries and other international organizations.Keywords: Caricature, Critical Discourse Analysis, Humanitarian Conflict, Norman Fairclough